2006
DOI: 10.1590/s0102-311x2006000200021
|View full text |Cite
|
Sign up to set email alerts
|

Ensaio clínico randomizado: efetividade da abordagem cognitivo-comportamental e uso de adesivos transdérmicos de reposição de nicotina, na cessação de fumar, em adultos residentes no Município do Rio de Janeiro, Brasil

Abstract: Randomized clinical trial carried out to investigate the effectiveness of the cognitive-behavioral approach and nicotine replacement therapy with nicotine patches for smoking cessation. Participated 1,199 adults, volunteers, in Rio de Janeiro, Brazil, randomly assigned to 10 different groups: intensive brief counseling group (GB), with 1 or 2 sessions (G1-G2), and with 3 or 4 sessions (G3-G4), with/without nicotine replacement therapy (NRT). Abstinence proportions were estimated during 12 months. These proport… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
13

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 14 publications
0
4
0
13
Order By: Relevance
“…Possivelmente, com o passar do tempo essa taxa será ainda maior, pois existe a tendência de aumentarem as recaídas quanto maior for o tempo de acompanhamento dos pacientes analisados com determinada terapêutica empregada 21 . Outros autores relataram taxas de fracasso semelhantes às aqui encontradas, em torno de 66,6% a 69%, e concluíram que aqueles com dificuldades de adesão ao tratamento e que não pararam de fumar nas primeiras semanas têm mais chances de fracassar [22][23][24] . Diversos fatores dificultadores da cessação devem estar interagindo com esses pacientes estudados.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Possivelmente, com o passar do tempo essa taxa será ainda maior, pois existe a tendência de aumentarem as recaídas quanto maior for o tempo de acompanhamento dos pacientes analisados com determinada terapêutica empregada 21 . Outros autores relataram taxas de fracasso semelhantes às aqui encontradas, em torno de 66,6% a 69%, e concluíram que aqueles com dificuldades de adesão ao tratamento e que não pararam de fumar nas primeiras semanas têm mais chances de fracassar [22][23][24] . Diversos fatores dificultadores da cessação devem estar interagindo com esses pacientes estudados.…”
Section: Discussionunclassified
“…14,15 : consiste de uma lista com 21 itens que são afirmações descritivas de sintomas de ansiedade e mede a intensidade deles (alfa de Cronbach = 0,92). A pontuação dos sintomas varia entre 0 e 63, e os resultados podem ser: mínimo (0-10), leve (11)(12)(13)(14)(15)(16)(17)(18)(19), moderado (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) e grave (31-63). Para fins de análise, a amostra foi dicotomizada, estabelecendo que a pontuação de 0 a 19 fosse caracterizada como mínima e/ou leve e a acima de 20 foi considerada como moderada a grave, assim como estudo prévio 16 .…”
Section: Introductionunclassified
“…Details on random allocation, calculation of sample size and intervention can be observed in a previous publication. 3 Data of the randomized trial have been compared to those of the "Household survey on risk behaviors and reported morbidity for non communicable diseases", a cross-sectional population-based study conducted …”
Section: Methodsmentioning
confidence: 99%
“…Several studies have compared the eligibility profile of study participants; who were recruited with that of smokers in general, overlooking that the profiles of study participants and smokers in general can differ (see, e.g., Otero et al 50 and West et al 51 ).…”
Section: Limitationsmentioning
confidence: 99%